Management of Water Quality in Moldova - Duca, Gheorghe (Water Science and Technology Library, 2014)
This book deals with water management, one of the most challenging issues of contemporary society. Research and innovation in the field of water management must address certain fundamental aspects: access to water, water quality, water treatment, transboundary effect of water, etc. A comprehensive analysis was performed in a national research program of Moldova, entitled "Research and management of water quality". The main goal of the research program was to create and improve the legal, scientific and methodological, technological basis and sustainable development of water, implementation of modern technologies in water supply, treatment and reuse. Other priorities include expansion of access to water sources, improvement of environmental protection, especially water protection against pollution and depletion, efficient water use and  establishing an effective monitoring system for disaster prevention. The topics concern research of water structure and quality, surface water, groundwater, water treatment, irrigation technologies and water pollution by remains from industry, one of the main environmental problems of our time. The book helps to get to coherent water policies of states.